Наратологічний аналіз роману Барбари Редінґ «Безумці» - Хамедова, Ольга; Khamedova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено наративну структуру роману Барбари Редінґ «Безумці», з’ясовано особливості функціонування всіх елементів наративу. Визначено, що у творі домінує суб’єктивна манера оповіді (форма діалогізованого монологу). Для наративу визначальний прийом текстової інтерференції. Авторську стратегію викладу реалізовує дієгетичний наратор, який часто виявляється обмеженим у своєму знанні, і тоді виклад підтримується всезнаючим недієгетичним наратором. The article explores narrative structure in the novel «Mad Men» by a contemporary Ukrainian writer Barbara Reding. Features of functioning narrative elements are determined. The subjective manner of presentation (dialogized monologue form) dominates in the novel. Text reception interference is determining factor in the narrative when text character and the actual presentation of combined text narrator. In the novel this type of narrator is modeled which affects the process of perception and interpretation of work. Diegetic narrator realized author strategy presentation. He is often limited in their knowledge, but in this case presentation supported by omniscient non-diegetic narrator. Reception is the principal internal focalization, but external focalization used too: the narrator is closely watching the heroes, captures their gestures, facial expressions, intonation, emotional reactions.
Narratologic Analysis of the Novel Barbara Reading «Mad Men»
Keywords: наратив; наратор; суб’єктивна манера оповіді; діалогізований монолог; narrator; narration; subjective manner of presentation; dialogized monologue; author strategy presentation; авторська стратегія викладу